The Influence of Work Ethic and Infrastructure on Employee Performance with Motivation as an Intervening Variable in Baznas Takalar Regency - Aldi Klarisa; Idris Parakkasi; Muhammad Nasri Katman (Journal AGENCY, 2025)
The factor that influences the level of success of an organization is the performance of its employees. The research aims to describe the influence of work ethic and infrastructure on employee performance with motivation as an intervening variable at BAZNAS Takalar Regency. This research uses a quantitative approach, using primary data, namely taking data from distributing questionnaires. The sampling technique in this research is a saturated sampling technique so the number of samples used is 100 people. The data analysis technique in this research uses (SEM) structural equation modeling using the help of SmartPLS to be able to solve the problem formulation and hypotheses that have been formulated in this research and is used to test the relationship between variables. The results of the research show that work ethic has a positive and significant effect on employee performance, work ethic has a positive and significant effect on motivation, motivation has a positive and significant effect on employee performance, infrastructure has a positive and significant effect on employee performance, infrastructure has no effect on motivation, there is There is an indirect influence between work ethic on employee performance through motivation as an intervening variable, and there is no indirect influence between infrastructure and facilities on employee performance through motivation as an intervening variable at BAZNAS Takalar Regency. The implication of this research is that for BAZNAS Takalar Regency, it can improve employee performance by developing and strengthening the work ethic among employees. As well as, optimizing infrastructure to increase employee comfort and work efficiency.